Main drivers of marine heat waves in the eastern South Pacific - David Carrasco; David Carrasco; Oscar Pizarro; Oscar Pizarro; Martín Jacques-Coper; Martín Jacques-Coper; Martín Jacques-Coper; Diego A. Narváez; Diego A. Narváez (Frontiers in Marine Science, 2023)
During the last decades, marine heat waves (MHWs) have increased in frequency and duration, with important impacts on marine ecosystems. This trend has been related to rising global sea surface temperatures, which are expected to continue in the future. Here, we analyze the main characteristics and possible drivers of MHWs in the eastern South Pacific off Chile. Our results show that MHWs usually exhibit spatial extensions on the order of 103-104 km2, temperature anomalies in the mixing layer between 1 and 1.3°C, and durations of 10 to 40 days, with exceptional events lasting several months. In this region, MHW are closely related to the ENSO cycles, in such a way that El Niño and, to a lesser extent, La Niña events increase the probability of high intensity and extreme duration MHWs. To analyze the MHW drivers, we use the global ocean reanalysis GLORYS2 to perform a heat budget in the surface mixed layer. We find that most events are dominated by diminished heat loss –associated with reduced evaporation– and enhanced insolation; thus, this group is called ASHF (for air-sea heat fluxes). The second type of MHWs is driven by heat advection, predominantly forced by anomalous eastward surface currents superimposed on a mean westward temperature gradient. The third type of MHWs results from a combination of positive (seaward) anomalies of air-sea heat fluxes and heat advection; this group exhibits the greatest values of spatial extension, intensity, and duration.